Watching Others Receive Unearned Superior Treatment: Examining the Effects on Tourists Who Receive Less Than Their Peers. (September 2019) - Colliander, Jonas; Söderlund, Magnus; Marder, Ben
Different treatment of different customers has traditionally been seen as a typical characteristic of tourism services. This research investigates unearned superior treatment in the tourism industry as taking place in a social setting where customers are able to compare the service they receive to that of other customers. Moreover, we take the disadvantaged customers' point of view and investigate the reactions of customers who receive comparably less than others in such situations. Our results indicate that those customers who receive less than others perceive the service exchanges as more unjust and therefore report lower levels of customer satisfaction and repatronizing intentions as well as higher levels of intentions to talk to others about their experiences. We further investigate whether decisions made by a single versus a group of employees affect the justice perceptions of the encounter. Implications for both research and practice are discussed.